Fuzzy clustering neural networks for real-time odor recognition system - Karlık, Bekir; Yüksek, Kemal (Hindawi Publishing Corp, 315 Madison Ave 3Rd Flr, Ste 3070, New York, Ny 10017 USA, 2007)
The aim of this study is to develop a novel fuzzy clustering neural network (FCNN) algorithm as pattern classifiers for real-time odor recognition system. In this type of FCNN, the input neurons activations are derived through fuzzy c mean clustering of the input data, so that the neural system could deal with the statistics of the measurement error directly. Then the performance of FCNN network is compared with the other network which is well-known algorithm, named multilayer perceptron (MLP), for the same odor recognition system. Experimental results show that both FCNN and MLP provided high recognition probability in determining various learn categories of odors, however, the FCNN neural system has better ability to recognize odors more than the MLP network. Copyright (c) 2007
Keywords: Electronic Nose; Architecture; Recorder